2017
DOI: 10.1016/j.cobeha.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

The adolescent brain at risk for substance use disorders: a review of functional MRI research on motor response inhibition

Abstract: Youth with family history (FH+) of substance use disorders (SUDs) are at increased risk for developing SUDs. Similarly, childhood attention deficit hyperactivity disorder (ADHD) is considered to be a risk factor for developing SUDs. Recent research has suggested a close association between SUDs and impaired inhibitory control. As such, it is crucial to examine common and distinct neural alterations associated with inhibitory control in these at-risk groups, particularly prior to the initiation of heavy substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…The effects of MAOA on ACC activation patterns are sex-dimorphic; specifically, MAOA-L male and MAOA-H female carriers with a history of early stress display impairments in the activation of the ACC in response inhibition (Holz et al, 2016), a process directly related to self-regulation (Posner and Rothbart, 1998;Blair and Ursache, 2011;Hofmann et al, 2012). It should be noted that functional deficits of the ACC are associated with a reduction in inhibitory control (Bush et al, 2000;Chan et al, 2011), as well as a facilitation of ventral striatal responses to incentive stimuli, which in turn increases drug use propensity (Holmes et al, 2016;Koyama et al, 2017). Notably, these deficits may be particularly overt in young individuals (and therefore highly relevant in the age range of college students), due to their incomplete myelination of the ACC as well as the development of the dopaminergic system, which further exacerbates their proclivity to engage in impulsive and risky actions and heightens their reward sensitivity (Casey et al, 2008;Steinberg, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of MAOA on ACC activation patterns are sex-dimorphic; specifically, MAOA-L male and MAOA-H female carriers with a history of early stress display impairments in the activation of the ACC in response inhibition (Holz et al, 2016), a process directly related to self-regulation (Posner and Rothbart, 1998;Blair and Ursache, 2011;Hofmann et al, 2012). It should be noted that functional deficits of the ACC are associated with a reduction in inhibitory control (Bush et al, 2000;Chan et al, 2011), as well as a facilitation of ventral striatal responses to incentive stimuli, which in turn increases drug use propensity (Holmes et al, 2016;Koyama et al, 2017). Notably, these deficits may be particularly overt in young individuals (and therefore highly relevant in the age range of college students), due to their incomplete myelination of the ACC as well as the development of the dopaminergic system, which further exacerbates their proclivity to engage in impulsive and risky actions and heightens their reward sensitivity (Casey et al, 2008;Steinberg, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of MAOA on ACC activation patterns are sex‐dimorphic; specifically, MAOA‐L male and MAOA‐H female carriers with a history of stress were shown to exhibit alterations in the activation of the ACC in response inhibition tasks . Functional impairments of the ACC (such as those predicted by the interaction of childhood stress and either MAOA‐H females or MAO‐L alleles in males) have been shown to lead to poor inhibitory control and increase substance use predisposition by facilitating the responses of the ventral striatum to incentive stimuli . From this perspective, it is likely that these deficits in inhibitory control may arguably facilitate use of cannabis and tobacco in adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…112 Functional impairments of the ACC (such as those predicted by the interaction of childhood stress and either MAOA-H females or MAO-L alleles in males) have been shown to lead to poor inhibitory control 113,114 and increase substance use predisposition by facilitating the responses of the ventral striatum to incentive stimuli. 115,116 From this perspective, it is likely that these deficits in inhibitory control may arguably facilitate use of cannabis and tobacco in adolescence. Thus, our studies may suggest that sex-dimorphic interactions of MAOA alleles and early maltreatment may facilitate inhibitory dyscontrol in adolescence and/or early adulthood, ultimately increasing the risk for tobacco smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory control is one component of higher‐order executive functions (Giedd et al, 1999; Gogtay et al, 2004). It is subserved by neural circuitry in the fronto‐basal ganglia network (Koyama et al, 2017; Lopez‐Caneda et al, 2014), which includes the prefrontal (PFC) and inferior frontal cortices (IFC), the presupplementary motor area, basal ganglia, and primary motor cortex (Aron, 2011). Typically developing children exhibit progressive reductions in neural network activation across the medial and lateral parts of the PFC and age‐related increases in the IFC and insula that are associated with improved inhibitory control performance (Casey et al, 1997; Somerville et al, 2011; Tamm et al, 2002).…”
mentioning
confidence: 99%
“…Preliminary functional magnetic resonance imaging (fMRI) research, utilizing the Go/NoGo Task, suggests that FH+ youth may have altered development of the fronto‐basal ganglia network. Some studies have reported reduced activation among FH+ youth in the right ventral and lateral parts of the PFC (Koyama et al, 2017), and the fronto‐parietal regions (Schweinsburg et al, 2004), while others have reported greater activation among FH+ youth in the ventral caudate (Heitzeg et al, 2010) and frontal regions (Acheson et al, 2014b), when compared to FH− youth. Furthermore, longitudinal research has suggested that alcohol‐naïve FH+ youth show increasing anterior cingulate activity over time, while their FH− peers showed the expected reduction in fronto‐striatal response to the Go/NoGo Task (Hardee et al, 2014).…”
mentioning
confidence: 99%